Cognitive Development (Symbolic Thinking) of Early Childhood Through the Innovation of Bowling Media - Fitri Galih Ramdhani; Leli Fertiliana Dea (Journal of Childhood Development, 2021)
The use of bowling media in RA Muslimat NU 1 Tulus Rejo Kec. Pekalongan has not been used. Researchers are interested in developing bowling media with the aim of developing cognitive, because early childhood in RA Muslimat NU 1 Tulus Rejo Kec. Pekalongan in terms of cognitive ability is still undeveloped. The purpose of this study is to find out the development of Media Bowling Against Cognitive Development (Symbolic Thinking) Early Childhood. This research methodology uses (research and development). The development procedure according to Borg and Gall's theory consists of seven stages. Based on the results of the study it can be concluded that, the use of bowling media in children aged 5-6 years in RA Muslimat NU 1 Tulus Rejo Kec. Pekalongan can improve children's cognitive abilities.